Mechanical Properties of Sustainable Base Course Binder Incorporating GGBFS and Spent FCC Catalyst - Rasheed, Sajjad E.; Hassan, Waqed H.; Fattah, Mohammed Y. (Salehan Institute of Higher Education, 2025)
This study investigates the feasibility of utilizing ground granulated blast furnace slag (GGBFS) and spent fluid catalytic cracking (FCC) catalyst as partial cement replacements in pavement base course materials. Various blends of GGBFS and FCC catalyst were evaluated as binders for unbound granular base (UGB) material, with total binder content fixed at 10% by weight. Mechanical properties were assessed through unconfined compressive strength (UCS) and splitting tensile strength tests at 3, 7, 28, and 56 days. Microstructural analysis was conducted using scanning electron microscopy (SEM) and X-ray diffraction (XRD). Results indicate that an optimal blend of 60% FCC and 40% GGBS achieved the highest UCS of 9.6 MPa at 56 days, exceeding typical requirements for cement-treated base materials. All investigated mix proportions surpassed the minimum 28-day strength requirement of 4 MPa for pavement base applications. Splitting tensile strength results corroborated compressive strength trends, with enhanced tensile-to-compressive strength ratios suggesting improved crack resistance potential. Microstructural analysis revealed a dense, well-reacted cementitious system supporting the observed mechanical performance. These findings demonstrate the technical feasibility and potential environmental benefits of incorporating high volumes of GGBS and spent FCC catalyst in pavement base materials, offering a sustainable alternative to conventional cement-based binders. Doi: 10.28991/CEJ-2025-011-03-012 Full Text: PDF